1981
DOI: 10.1080/02626668109490884
|View full text |Cite
|
Sign up to set email alerts
|

Long term responses of streamflow following clearcutting and regrowth / Réactions à long terme du débit des cours d'eau après coupe et repeuplement

Abstract: Long term changes in streamflow following forest cutting are presented for three experimental basins at Coweeta Hydrologie Laboratory, North Carolina, USA. Previous analyses have shown that, following forest cutting, streamflow increases and then declines with the logarithm of time as the forest regrows. Recent data indicate that the streamflow decline following cutting is related to vegetation regrowth, but the relationship is not a consistent function of simple stand measurements. The mixed hardwood forest o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In the 1950s and 1960s, several studies examining the role of LAI on discharge were conducted in various experimental watersheds, including Hubbard Brook in New Hampshire and Coweeta in North Carolina, and provided valuable information to municipal watershed managements. These studies concluded that the type and composition of vegetation cover influence discharge, primarily by finding that small changes in LAI in a watershed can produce large changes in discharge (Swank and Douglass, 1974;Swift and Swank, 1981;Bosch and Hewlett, 1982;Jones and Post, 2004;Brown et al, 2005;Bren and Hopmans, 2007). A positive relationship exists between LAI and rainfall interception (Kittredge, 1948;Lee, 1980;Hewlett, 1982;Chang, 2006).…”
Section: Water Resourcesmentioning
confidence: 99%
“…In the 1950s and 1960s, several studies examining the role of LAI on discharge were conducted in various experimental watersheds, including Hubbard Brook in New Hampshire and Coweeta in North Carolina, and provided valuable information to municipal watershed managements. These studies concluded that the type and composition of vegetation cover influence discharge, primarily by finding that small changes in LAI in a watershed can produce large changes in discharge (Swank and Douglass, 1974;Swift and Swank, 1981;Bosch and Hewlett, 1982;Jones and Post, 2004;Brown et al, 2005;Bren and Hopmans, 2007). A positive relationship exists between LAI and rainfall interception (Kittredge, 1948;Lee, 1980;Hewlett, 1982;Chang, 2006).…”
Section: Water Resourcesmentioning
confidence: 99%